2009
DOI: 10.1093/brain/awp255
|View full text |Cite
|
Sign up to set email alerts
|

Integration of gaze direction and facial expression in patients with unilateral amygdala damage

Abstract: Affective and social processes play a major role in everyday life, but appropriate methods to assess disturbances in these processes after brain lesions are still lacking. Past studies have shown that amygdala damage can impair recognition of facial expressions, particularly fear, as well as processing of gaze direction; but the mechanisms responsible for these deficits remain debated. Recent accounts of human amygdala function suggest that it is a critical structure involved in self-relevance appraisal. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
82
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 64 publications
14
82
2
Order By: Relevance
“…We confirm that activity within motorrelated cortical areas arises 150 -200 ms after the onset of a perceived action (Nishitani and Hari, 2002;Caetano et al, 2007;Tkach et al, 2007;Catmur et al, 2010) and that the interaction between gaze direction and emotion takes place at ϳ200 -300 ms (Klucharev and Sams, 2004;Rigato et al, 2010). However, in contrast to recent accounts of human amygdala function in social cue integration (Sander et al, 2007;NЈDiaye et al, 2009;Cristinzio et al, 2010;Sato et al, 2010), we found that emotional content is processed earlier within the amygdala and independently of other cues.…”
Section: Discussionsupporting
confidence: 78%
“…We confirm that activity within motorrelated cortical areas arises 150 -200 ms after the onset of a perceived action (Nishitani and Hari, 2002;Caetano et al, 2007;Tkach et al, 2007;Catmur et al, 2010) and that the interaction between gaze direction and emotion takes place at ϳ200 -300 ms (Klucharev and Sams, 2004;Rigato et al, 2010). However, in contrast to recent accounts of human amygdala function in social cue integration (Sander et al, 2007;NЈDiaye et al, 2009;Cristinzio et al, 2010;Sato et al, 2010), we found that emotional content is processed earlier within the amygdala and independently of other cues.…”
Section: Discussionsupporting
confidence: 78%
“…Such findings would suggest that specific neural structures are strongly activated when the combination of eye gaze direction and facial expressions give rise to unambiguous, self-relevant threats (e.g., Cristinzio et al 2010). In apparent contrast with these data, showed that angry faces coupled with averted gaze and fearful faces coupled with direct gaze (ambiguous threat) elicited stronger amygdala activations than angry faces coupled with direct gaze and fearful faces coupled with averted gaze (unambiguous threat).…”
Section: Discussionmentioning
confidence: 82%
“…That is, eye-gaze direction of fearful faces may play a key role in arousal and threat processing, as is suggested by neuroimaging evidence in healthy (Wicker et al, 2003) and lesioned (Cristinzio et al, 2010) participants. While Sato et al (2011a) showed that both direct and averted gaze elicited differential amygdala neuronal activity, they did not control for emotion.…”
Section: Affective Processingmentioning
confidence: 82%